2000
DOI: 10.1007/s10434-000-0669-6
|View full text |Cite
|
Sign up to set email alerts
|

Total Gastrectomy With Dissection of Lymph Nodes Along the Splenic Artery: A Pancreas-Preserving Method

Abstract: The pancreas-preserving method described here was superior to the more common pancreas resecting method with regard to surgical risk and postoperative glucose tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 15 publications
0
29
0
3
Order By: Relevance
“…The study by Okinaga et al [30] was comparatively much smaller, and again, no significant difference in overall survival with spleen preservation was demonstrated. Furukawa et al [27] also found no statistically significant increase in the reported fistula or leaks rate, and no difference in overall survival in patients Significance corresponds to the noted superscripts AL anastomotic leakage, N number, MNS mean survival, MS median survival, NR not reported, PF pancreatic fistula, PR pancreaticosplenectomy, pts patients, R0 resection with no residual tumor, SP spleen-preserving, SR splenectomy S94 S. S. Brar et al…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The study by Okinaga et al [30] was comparatively much smaller, and again, no significant difference in overall survival with spleen preservation was demonstrated. Furukawa et al [27] also found no statistically significant increase in the reported fistula or leaks rate, and no difference in overall survival in patients Significance corresponds to the noted superscripts AL anastomotic leakage, N number, MNS mean survival, MS median survival, NR not reported, PF pancreatic fistula, PR pancreaticosplenectomy, pts patients, R0 resection with no residual tumor, SP spleen-preserving, SR splenectomy S94 S. S. Brar et al…”
Section: Discussionmentioning
confidence: 92%
“…In the retrospective studies, spleen preservation was associated with improved survival in 8 studies, diminished survival in 1 study, and no statistically significant difference in survival in 12 studies (Tables 3, 4, 5). In the one RCT comparing patients who underwent extended lymphadenectomy with or without pancreas preservation, there was no statistically significant difference in overall survival [27] (Table 1). …”
Section: Overall Survivalmentioning
confidence: 98%
See 2 more Smart Citations
“…In these randomized trials from Chile [8], Korea [9], and Japan [10], researchers reported no survival benefit from splenectomy in patients with a total gastrectomy, whereas morbidity was increased. A meta-analysis of operative survival with the data from these randomized trials showed no statistically significant difference (OR, 1.59; 95 % CI, 0.44-5.79) [11].…”
mentioning
confidence: 99%